75=-3(-6f-5)

Simple and best practice solution for 75=-3(-6f-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 75=-3(-6f-5) equation:



75=-3(-6f-5)
We move all terms to the left:
75-(-3(-6f-5))=0
We calculate terms in parentheses: -(-3(-6f-5)), so:
-3(-6f-5)
We multiply parentheses
18f+15
Back to the equation:
-(18f+15)
We get rid of parentheses
-18f-15+75=0
We add all the numbers together, and all the variables
-18f+60=0
We move all terms containing f to the left, all other terms to the right
-18f=-60
f=-60/-18
f=3+1/3

See similar equations:

| 1/2(4-6x)=23 | | 27x+78=27x+11 | | 1(4-x)=-3+-1 | | 17-u=-9u+9u-1 | | -6(u+66)=66 | | F(7)=2x-1 | | 18=5h–2 | | 2y+72=43 | | 1(4-x)=-3+-5 | | -6(u+66)=6 | | (3x-2/4)=2x-8 | | 3x-15=2x÷10 | | 7q+13=8q | | 1(4-x)=-3+-7 | | 2n^2-9n+11=0 | | 3d+8=18+2d | | 1(4-x)=-3+9 | | 10n+3=-57 | | 2f^2-6f-6=2 | | 1+2p=17 | | 7x+8x-4=3(5x+5) | | -120=-2x+6(7x+20) | | 1(4-x)=-3+-9 | | -20-k=2K+18+19 | | 2z+-37z=-29 | | -4(2x+10)=2x-8-2 | | n-22/8=5 | | 1(4-x)=-3+5 | | h+7=18 | | 1*2^x=100000 | | ⅓x+6=12 | | 5(4-x)=-3+-9 |

Equations solver categories